Role of Jawarish Amla as an adjunct to anti-tuberculosis drugs in the symptomatic relief of pulmonary tuberculosis - Rahmathulla; Sherwani, Arish Mohammad Khan; Husain, Safder (International Journal Of Community Medicine And Public Health, 2024)
Background: Tuberculosis is a global emergency, with approximately nine million people developing the disease every year. India has the highest TB burden worldwide, accounting for nearly one-fifth of the global burden. DOTS provides an 85% cure rate and symptomatic relief during therapy. However, it has been observed that some troubleshooting symptoms persist during the regimen; therefore, testing and providing a pharmacologically multipotent herbal adjuvant drug can improve compliance with DOTS chemotherapy. Methods: This study was conducted to explore whether any benefits could be achieved by adding Jawarish Amla to conventional anti-tubercular chemotherapy. Forty patients with pulmonary tuberculosis were enrolled to evaluate the efficacy of Jawarish Amla as adjuvant therapy. Patients were randomly assigned to the control and test groups, with 20 patients in each group. Jawarish Amla was administered to the test group for 60 days along with DOTS and the control group received a placebo with DOTS; for the same duration. Results: The test drug exhibited statistically significant improvement in almost all parameters, especially appreciated in weight gain (p<0.046), hemoptysis (p<0.0069), breathlessness (p<0.0015), nausea (p<0.001) vomiting (p<0.001), abdominal pain (p<0.001), itching (p<0.001), burning sensation in feet (p<0.001), jaundice (p<0.001), Hb% (p<0.001), ESR (p<0.010), SGOT (p<0.034), SGPT (p<0.020), alkaline phosphatase (p<0.007) and total bilirubin (p=0.069+). Conclusions: These results indicate that the test drug is safe and effective and especially checks the adverse effects of anti-tubercular drugs used in DOTS therapy. Thus, it can be used as an excellent adjuvant along with DOTS in community management of diqqe revi (pulmonary tuberculosis).